Вплив складу регенераційних поживних середовищ на регенерацію пшениці твердої в культурі пиляків in vitro - Доброва, Г.О.; Замбріборщ, І.С.; Шестовал, О.Л. (Фактори експериментальної еволюції організмів, 2015)
Aims. Green haploid plant regeneration is the last stage of anther culture method. Thus it is highly important to consider
the effect of regeneration cultural media composition on the level of spring and winter durum wheat hybrids regeneration.
Methods. C17, N6, MS regeneration cultural media were used. The percentage of regenerated plants per number of
newformations and confidence interval were calculated. Results. The influence of hormonal and organic components
addition to the cultural media C17, N6, MS on the plant regeneration level were determined. Spring and winter hybrids
were compared. Green haploid plants on spring durum wheat hybrids were obtained on MS media. Winter durum wheat
hybrids were not sensitive to the cultural condition. Green plants of only one genotype were regenerated on C17 and
N6 media without malic acid addition. Conclusions. Spring durum wheat hybrids were more sensitive to the anther
culture condition then winter hybrids. The most appropriate regeneration cultural media for spring hybrids were MS2
with proline and glutamine addition and BAP as cytokinin addition. Malic acid addition suppress the plants regeneration.
Keywords: durum wheat, regeneration in vitro, anther culture, cultural media.